Elitutbildning: en strategi för erkännande? En studie om anti-diskrimineringsstrategier bland juriststudenter med ursprung i Mellanöstern (Sociologisk Forskning, 2011)
Elite Education: a strategy for recognition? A study on anti-discrimination strategies among law-students of Middle Eastern backgroundWhile research show that individuals of foreign background are being discriminated against and stigmatized in Sweden, an increasing number of them still choose higher education and also show a tendency towards choosing an elite education. In this article, I examine if there is a link between experiences of discrimination and the choice of elite education. The study is based upon semi-structured interviews with five female and five male law students of Middle Eastern background. The findings show that discrimination, either against the students or their parents, has led to a high study motivation where the choice of elite education can be understood as an anti-discrimination strategy. Other anti-discrimination strategies are to resist a victim mentality and to destigmatize by challenging stereotypes. These anti-discrimination strategies can be understood as strategies for recognition, that is, striving for equality by being ascribed a positive status.